2005
DOI: 10.1021/es048319x
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Anthropogenic Silver Cycle:  A Multilevel Analysis

Abstract: Anthropogenic cycling of silver in 1997 is presented using three discrete governmental units: 64 countries encompassing what we believe to be over 90% of global silver flows, 9 world regions, and the entire planet. Using material flow analysis (MFA) techniques, the country level cycles are aggregated to produce the regional cycles, which are used to form a "best estimate" global cycle. Interesting findings include the following: (1) several silver-mining countries export ore and concentrate but also import sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 19 publications
0
62
0
1
Order By: Relevance
“…It is likely that the lost indium is in the mining tailings and the sludge from smelters. The yield rates for other metals were estimated as follows: 86% for copper, 26) 73% for silver, 27) 73% for chromium, 28) 82% for zinc 7) and 87% for nickel. 29) These figures demonstrate that the yield rate for indium is significantly lower than those for other metals, which may be attributed to the difficulty of extracting indium compared with other metals.…”
Section: Analysis Of Indium Flow In Mining Smelting Andmentioning
confidence: 99%
“…It is likely that the lost indium is in the mining tailings and the sludge from smelters. The yield rates for other metals were estimated as follows: 86% for copper, 26) 73% for silver, 27) 73% for chromium, 28) 82% for zinc 7) and 87% for nickel. 29) These figures demonstrate that the yield rate for indium is significantly lower than those for other metals, which may be attributed to the difficulty of extracting indium compared with other metals.…”
Section: Analysis Of Indium Flow In Mining Smelting Andmentioning
confidence: 99%
“…Silver compounds are used for the coating of photographic and X-ray film. Photography materials are the major source of discarded silver [13]. Silver can enter your body through your skin, such as photographers touching powders with silver in them.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the information provide a base and support to design and make resource policies; many research fields are involved in the following: (1) analysis of quantities in the entire system-Chen researched the whole life cycle of aluminum including production, trade, consumption, stocks, and losses using the SFA method [8][9][10]15,29]; Buchner analyzed Austrian aluminum flows in 2010 using a static SFA model and conducted extensive research on aluminum production, consumption, trade, and waste management [30]; (2) recycling and sustainability-Melo developed several models (statistical approaches) for estimating the potential scrap arising from discard metal-containing products to predict the amount of aluminum old scrap in the waste management stage in Germany [31]; Boin and Bertram carried out mass balance analysis in the aluminum recycling industry for the EU-15 in 2002 [32]; Hatayama et al reported a dynamic SFA of aluminum and its alloying elements in Japan to estimate future quantities of discarded aluminum in each of the eight categories using a population balance model [33]; (3) combining with other aspects such as value chain and environment; Dhalström analyzed aluminum flows in the United Kingdom in 2001 combining SFA with economic and environmental dimensions to create a value chain analysis [34]; Gang developed a dynamic SFA model to simulate the stocks and flows of the U.S. aluminum cycle and analyze the corresponding greenhouse gas (GHG) emissions [13]. Of course, this wonderful methodology was also conducted to research other metals, such as copper [35][36][37][38][39][40], nickel [41], zinc [39,42,43], iron [26], lead [44,45], silver [46], phosphorus [47,48], and so on. In recent years, this method has been applied at a more micro level, and used to measure the recovery rate, recovery amount, and recovery potential of a certain kind of product within a region or a small area [49][50]…”
Section: Substance Flow Analysis (Sfa) and Brief Literature Reviewmentioning
confidence: 99%